The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pen.25734
|View full text |Cite
|
Sign up to set email alerts
|

Envelopes with microplastics generated from recycled plastic bags for crude oil sorption

Abstract: Oil spill accidents in marine environments and the lack of disposal of post‐consumer plastic are environmental problems worldwide. This study presents a sustainable alternative for both issues through envelopes filled with microplastics (MPs) from recycled bags for the sorption of spilled crude oil. Through particle size analysis by three different sieves (4, 9, and 20 mesh), different MP sizes were characterized by scanning electron microscope (SEM), Brunauer–Emmett–Teller (BET), density, contact angle (CA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…It may be possible that the oil is trapped in the porous interior structure of the GTL powder. The results of this research agree with previous research by Li et al who reported that a PLA fiber mat can remove the motor, crude, and diesel oils from water 35 and Martins et al also reported that plastic bag waste can adsorb crude oils 36 . Moreover, the oil sorption capacity of the composite fibers tends to increase slightly after adding a masterbatch of Ag/GTL.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It may be possible that the oil is trapped in the porous interior structure of the GTL powder. The results of this research agree with previous research by Li et al who reported that a PLA fiber mat can remove the motor, crude, and diesel oils from water 35 and Martins et al also reported that plastic bag waste can adsorb crude oils 36 . Moreover, the oil sorption capacity of the composite fibers tends to increase slightly after adding a masterbatch of Ag/GTL.…”
Section: Resultssupporting
confidence: 91%
“…The results of this research agree with previous research by Li et al who reported that a PLA fiber mat can remove the motor, crude, and diesel oils from water 35 and Martins et al also reported that plastic bag waste can adsorb crude oils. 36 Moreover, the oil sorption capacity of the composite fibers tends to increase slightly after adding a masterbatch of Ag/GTL. Particularly, the PLA-3 composite fiber showed the highest oil sorption capacity at up to 9.08 g/g.…”
Section: Oil Sorption Capacitymentioning
confidence: 99%